2020
DOI: 10.1017/s000711452000450x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional implications of dietary gluten avoidance among Canadians: results from the 2015 Canadian Community Health Survey

Abstract: Adherence to a gluten-free diet (GFD) is the only available treatment for gluten-related disorders, although a GFD may also be followed for discretionary reasons. The main objectives of this study were to 1) describe and test for differences in key nutrient intakes among Canadians who follow a GFD compared to Canadians with no dietary exclusions; and 2) describe additional dietary avoidances, such as meat, poultry, fish, shellfish, eggs or dairy, adhered to by Canadians who avoid gluten. We conducted a seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…A recent large survey in Australia reported that 24% of participants were avoiding wheat (gluten), half of whom were doing so as they perceived it to be better for their general health ( 12 ). Similarly, a Canadian survey found that 1.9% of Canadians follow a gluten-free diet, and those who did so had lower intakes of iron, calcium, folate, B12 and Vitamin D than those who were eating wheat ( 28 ). In our cohort, wheat was significantly more likely to be avoided by those with no FA, which is consistent with findings from other studies of individuals with conditions such as irritable bowel syndrome ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent large survey in Australia reported that 24% of participants were avoiding wheat (gluten), half of whom were doing so as they perceived it to be better for their general health ( 12 ). Similarly, a Canadian survey found that 1.9% of Canadians follow a gluten-free diet, and those who did so had lower intakes of iron, calcium, folate, B12 and Vitamin D than those who were eating wheat ( 28 ). In our cohort, wheat was significantly more likely to be avoided by those with no FA, which is consistent with findings from other studies of individuals with conditions such as irritable bowel syndrome ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been reported that strict gluten-free diets in coeliac, after one year of maintenance, counteract Zn deficiencies and do not require longterm supplementation [30]. In the Canadian population it was found that subjects who avoided gluten in their diet did not have deficient Zn intakes compared to those who did not avoid any food group, which could be related to the fact that the former were more likely to consume mineral and vitamin supplements in the last 30 days prior to the study [32].Therefore, it would be advisable to recommend that GRD-CH treated with gluten-free diets consume foods with higher Zn content and Zn-BA, which, based on the present study, could be nuts, dairy products, vegetables, lamb, legumes and beef (Table 1), as well as non-gluten cereals. Furthermore, in gluten-free diets, rice is usually the most consumed grain, for which a low Zn intake has been indicated [33].…”
Section: Zn-ba Of Foods In In Children With Gluten Related Disordersmentioning
confidence: 97%
“…Most people are here nowadays engaging in Vegan, nutrient selection, gluten avoidance, and many other health-conscious eating decisions. Some are as a result of prescription by medical practitioners or as a sickness avoidance strategy (Mudryj et al 2021). In many developed and highly researched nations there is more preference for natural sugar instead of industrially produced sugar.…”
Section: The Community Health Of Agriculture-based Economiesmentioning
confidence: 99%